2019
DOI: 10.1002/mc.23003
|View full text |Cite
|
Sign up to set email alerts
|

Green tea–induced epigenetic reactivation of tissue inhibitor of matrix metalloproteinase‐3 suppresses prostate cancer progression through histone‐modifying enzymes

Abstract: Green tea polyphenols (GTPs) and their major constituent, epigallocatechin‐3‐gallate (EGCG), have been reported to demonstrate many interesting biological activities, including anticancer properties. Recent studies on prostate cancer provide strong evidence that epigenetic mechanisms are major players in the regulation of matrix metalloproteinases (MMPs) and their binding partner tissue inhibitor of MMPs (TIMPs) involved in prostate cancer progression. Here we demonstrate that GTP/EGCG mediate epigenetic react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 46 publications
3
27
0
Order By: Relevance
“…Essentially, green tea polyphenols and EGCG treatment significantly reduced class I histone deacetylases (HDAC) activity/expression in prostate cancer cells. Furthermore, levels of EZH2 and H3K27me3 were also found to be reduced in prostate cancer cells [25]. Data clearly suggested that EGCG efficiently demonstrated multi-layered regulation of HDACs and EZH2.…”
Section: Regulation Of Methylation-associated Machinerymentioning
confidence: 83%
See 1 more Smart Citation
“…Essentially, green tea polyphenols and EGCG treatment significantly reduced class I histone deacetylases (HDAC) activity/expression in prostate cancer cells. Furthermore, levels of EZH2 and H3K27me3 were also found to be reduced in prostate cancer cells [25]. Data clearly suggested that EGCG efficiently demonstrated multi-layered regulation of HDACs and EZH2.…”
Section: Regulation Of Methylation-associated Machinerymentioning
confidence: 83%
“…There was a considerable reduction in the levels of enhancers of zeste homolog 2 (EZH2) and H3K27me3 repressive marks at the promoter region of TIMP-3. Additionally, there was an evident increase in histone H3K9/18 acetylation [25]. Essentially, green tea polyphenols and EGCG treatment significantly reduced class I histone deacetylases (HDAC) activity/expression in prostate cancer cells.…”
Section: Regulation Of Methylation-associated Machinerymentioning
confidence: 99%
“…As described above, Deb et al analyzed the amount of TIMP3 in plasma samples after polyphenon E treatment in patients in the period between tumor biopsy and radical prostatectomy. HDAC 1 activity, EZH2, and trimethylations in H3K27 were reduced in GTPs supplemented prostate tissue [142]. Similarly, SFN demonstrated significant modulation properties via the regulation of PHMs in the clinical study, in which the level of HDAC activity was evaluated in healthy volunteers.…”
Section: Prostate Cancermentioning
confidence: 82%
“…Extensive oncological research demonstrated that plant natural compounds may be effective in targeting epigenetic alterations associated with the cancer promotion and progression as well as the primary chemoprevention by affecting the carcinogenesis in early stages during initiation [167]. A great amount of phytochemicals exerted anticancer activities via modulation of PHMs, as was demonstrated mainly in in vitro as well as in vivo preclinical studies focusing on BC, PC, and CRC [14,118,133,141,142,146,157,160,172]. However, the usefulness of phytochemicals within clinical approaches is not sufficiently investigated in this topic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation